Pemberi Pakan Kucing Otomatis Berbasis IOT: Penelitian - Rahmat; Dicky Apdillah; Zulfirman; Arinda Faradilla Marpaung (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The increasingly dynamic lifestyle of modern society has led to limited time for proper pet care, particularly in maintaining regular feeding routines for cats. Manual feeding practices often result in inconsistent schedules, inaccurate food portions, and difficulties in monitoring feeding activities when owners are away. This study aims to design and implement an Internet of Things–based automatic cat feeder as a solution to these challenges. The research employs a research and development approach, encompassing needs analysis, system design, hardware and software implementation, and functional testing. The developed system integrates an IoT-based microcontroller, a mechanical feeding mechanism, and an internet-based monitoring application. Experimental results indicate that the system is capable of dispensing food automatically according to predefined schedules with high time accuracy and stable portion consistency. Furthermore, the system allows remote control and monitoring with reliable responsiveness as long as an internet connection is available. These findings demonstrate that the proposed system effectively improves feeding efficiency, supports consistent feeding patterns for cats, and provides convenience and assurance for pet owners. The system also shows potential for further development in the field of smart pet care technologies.